Canadian Architectural Archives at the University of Calgary Libraries - Walker, Annalise (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
The Canadian Architectural Archives at the University of Calgary Libraries were established in 1974; first major collections were donated in 1975 and, by 1983, the Archives has grown significantly. Collections consist mostly of drawings, file material and photographs, with some models. The purpose of the Archives is support of study and research and preservation of documents. Major collections include those of John B. Parkin Associates, Arthur Erickson, and Ron Thorn, as well as other large collections from the Toronto, Calgary and Vancouver area. Organization of collections is based on archival principles of original order and provenance, and access to individual building projects is facilitated through various indices and inventories. An Oral History programme provides some additional biographical background. With a few exceptions, all materials are accessible for research in the Archives reader area; limited research assistance can be given to persons from out of town or out of province. Copies of individual items can be provided for research, exhibition or publication under strict copyright regulations.